Performance Enhancement of Solar Photovoltaic Cooling Using Water Sprinkler - Najwa Md Nasir, Nurul; Singh, Baljit; Abu Bakar, Raihan; Fairuz Remeli, Muhammad; Nanggar, Aneurin; Oberoi, Amandeep (International Journal of Engineering and Technology, 2018)
Solar energy is free and the most abundant renewable energy available today. Solar Photovoltaic (PV) cells are one of the medium to extract this energy. This project focuses on using forced convection water cooling with water sprinkler to cool overheated solar cells and to help reducing the surface temperature of the solar panel for optimum operation in terms of output power. The cooling method involved was a water-type forced convection method using water sprinkler system. The water will flow on the top surface of the panel and this promotes the reduction of temperature of the cells. This study is aimed to decrease the temperature therefore it will result in increment of open circuit voltage of the panel. The increment of the open circuit voltage helps to convert much more sufficient amount of solar energy into useful electrical energy. Moreover, it will increase the rate of efficiency of the PV panel. This project was conducted at the Green Energy Research Centre (GERC), Kolej Teratai, UiTM Shah Alam.Â